The influence of cultural norms in pragmatic interpretation in English and Uzbek: research on Speech acts and social interactions - Izbosarova, Xulkar (The Lingua Spectrum, 2025)
This article studies common pragmatic challenges faced by English and Uzbek languages speaker focusing on the influence of cultural norms and values on pragmatic interpretation in both languages. The research relied on a survey conducted among 94 final-year students of Uzbekistan State World Languages University majoring in English Language and Literature. The survey aimed at investigating the usage of speech acts such as expressions of gratitude, requests, offers of help, and apologies in various contexts, such as face-to-face and social media interactions. Quantitative and qualitative analysis were gathered by multiple-choice and open-ended questions created on Google Forms. Quantitative analysis revealed different patterns in pragmatic choices influenced by cultural factors, including the preference for indirect apologies (“uzur”) and expressive interjections in informal settings. The role of context, gesture use, and linguistic strategies, which were highlighted by qualitative approach, were discussed in different communicative scenarios. Moreover, the research examined how Uzbek speakers, especially youths adapt their language use on social media to convey various meanings. This study contributes to understand the need for culturally-informed approaches in language education.